Pengawasan dan Keseimbangan antara DPR dan Presiden dalam Sistem Ketatanegaraan RI - M. Arsyad Mawardi (Fakultas Hukum Universitas Islam Indonesia, 2008)
Among the goals of the 1945 constitution amendment is to create the balance among the legislative, executive and judicative powers, and thus the check and balance function may take place. So as the proposal for enhancing the authority of the parliament members, which is according to the second amendment hold the supervisory function as has been provided by section 20 (1).